A TERTÚLIA FILOSÓFICA NO ENSINO DE FILOSOFIA: Uma experiência prática de ensino no Instituto Estadual de Educação, Ciência e Tecnologia do Maranhão – IEMA Pleno Bacabeira - VIEIRA, Carmemylla Batista (2023)
The present study has the title: PHILOSOPHICAL TERTULIA IN THE TEACHING OF PHILOSOPHY: A practical teaching experience at the State Institute of Education, Science and Technology of Maranhão – IEMA Pleno Bacabeira. and as the specific objectives, build a philosophical reading practice in high school students taking into account their own reading universe; Encourage philosophical reading of classic works of Philosophy; Promote philosophy teaching that offers space for male and female students to take center stage; Present the philosophical gathering as a methodology to encourage philosophical reading in the discipline of Philosophy. Promote pedagogical situations to develop the cognitive skills necessary for students to solve the concrete problems they experience. This research is initially motivated by a concern that arises from my teaching practice with public high school students. Philosophical reading is one of the central points of discussion when we refer to the teaching of philosophy. Reading has been considered, in humanistic education, as the main tool for the conservation of tradition (memory of humanity) and of great relevance for the formation of individuals. Analyzing and discussing philosophical reading as a contemporary problem is necessary. Mainly because 21st century education is marked by the uncertainties of rapid transformations. From this perspective, school and economy are seen in an articulated way, focused on a utilitarian sense. On the one hand, the strong competition of a globalized space and on the other, the function of qualifying knowledge in the production of goods and services. Culture is fostered through the exact prescription of limits that ensure contradiction only within predictable patterns, in the case of mass culture and the interests of the labor market. Added to this problem is the desire to develop with students and other education professionals a reading methodology for teaching philosophy that encourages students and allows them to achieve autonomy. The methodology of philosophical gatherings offers support for the construction of philosophical school knowledge based on inclusive representations that can contribute to problem solving. To theoretically corroborate the research, Nietzschean thinking is used. In this conception, the philosopher Nietzsche observes the pedagogical importance of hermeneutics in the development of humanistic education to the detriment of technical education.